2016
DOI: 10.1007/s11523-016-0440-y
|View full text |Cite
|
Sign up to set email alerts
|

Safety and QOL in Patients with Advanced NET in a Phase 3b Expanded Access Study of Everolimus

Abstract: EudraCT no. 2010-023032-17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…The age of patients in this study is similar to that reported in the pivotal RADIANT-3 phase III clinical trial of everolimus [9] and a recent phase IIIb study that evaluated safety and HRQoL in patients with advanced NETs treated with everolimus in an expanded access protocol [17]. About 30% of patients in our study had a performance status of 0 at baseline, which is lower than the phase III trial (67%) [9] and expanded access study (56%) [17]. This difference may reflect the real-world nature of the OBLIQUE population, with patients limited in their everyday activities to a greater extent than patients included in clinical trials.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The age of patients in this study is similar to that reported in the pivotal RADIANT-3 phase III clinical trial of everolimus [9] and a recent phase IIIb study that evaluated safety and HRQoL in patients with advanced NETs treated with everolimus in an expanded access protocol [17]. About 30% of patients in our study had a performance status of 0 at baseline, which is lower than the phase III trial (67%) [9] and expanded access study (56%) [17]. This difference may reflect the real-world nature of the OBLIQUE population, with patients limited in their everyday activities to a greater extent than patients included in clinical trials.…”
Section: Discussionmentioning
confidence: 64%
“…everolimus [17]. A further patient reported outcome study in 44 outpatients (single-center in Italy) with PanNENs receiving either no treatment, or somatostatin analogs (with or without radiometabolic therapy) showed that over a 4-month period, patients had a good physical, but impaired mental component of HRQoL [11].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary toxicity (n=5) and infection/sepsis (n=3) were the most common fatal AEs that caused everolimus-related death[22,23,75,76,93]. Though patient-reported tolerance with everolimus treatment was reported to be poorer than SSA[165], health-related QOL was well maintained in large clinical trials[71,79,166]. These results strongly support the general tolerability of everolimus by most patients in both the clinical trial setting and real-world setting.…”
Section: Safety Of Everolimus (Table 6)mentioning
confidence: 99%
“…Ramage et al[ 54 ] used the EQ-5D-5L (in addition to EORTC QLQ-C30 and GINET21), with no significant difference for the composite health index or self-rated (global) health score noted between baseline and 6-mo treatment with everolimus. The EQ-5D VAS was employed in two studies: Kulke et al[ 55 ] examined patients receiving repeated 6-weekly cycles of oral sunitinib, noting no significant difference in VAS scores over the study period, whilst Pavel et al[ 56 ] reported a reduced mean VAS from baseline to end of treatment with oral everolimus (10 mg daily, in 28-d cycles) in non-P-NET patients (63.9 ± 19.0 vs 55.3 ± 23.0, respectively) compared to P-NET patients (68.8 ± 19.9 vs 66.5 ± 20.6, respectively). The FACIT-D measure is a symptom-specific measure used by Kvols et al[ 29 ] in a Phase II, open-label, multicentre prospective study of self-administered pasireotide.…”
Section: Resultsmentioning
confidence: 99%